2016
DOI: 10.1124/dmd.116.069336
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Analysis of Intestinal Transport in Enterocyte-Like Cells Differentiated from Human Induced Pluripotent Stem Cells

Abstract: We previously demonstrated that differentiated enterocytes from human induced pluripotent stem (iPS) cells exhibited drugmetabolizing activities and cytochrome P450 CYP3A4 inducibility. The aim of this study was to apply human iPS cell-derived enterocytes in pharmacokinetic studies by investigating the characteristics of drug transport into enterocyte-like cells. Human iPS cells cultured on feeder cells were differentiated into endodermal cells using activin A. These endodermal-like cells were then differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 37 publications
(32 reference statements)
3
17
0
Order By: Relevance
“…P-gp, BCRP, and PEPT1 play important roles in intestinal drug absorption. The functions of BCRP and PEPT1 in hiPSC-IECs have been previously reported (Iwao et al, 2015;Ogaki et al, 2015;Ozawa et al, 2015;Kodama et al, 2016;Uchida et al, 2017), whereas the present study is the first to reveal the functional expression of P-gp in hiPSC-IECs. The P app value of [ 3 H]digoxin (a P-gp substrate) in the basolateral-to-apical direction was greater than that in the apical-tobasolateral one (efflux ratio, 2.43), and the differences in P app in these two directions disappeared in the presence of cyclosporin A (efflux ratio, 0.743) (Fig.…”
Section: Downloaded Fromsupporting
confidence: 50%
See 2 more Smart Citations
“…P-gp, BCRP, and PEPT1 play important roles in intestinal drug absorption. The functions of BCRP and PEPT1 in hiPSC-IECs have been previously reported (Iwao et al, 2015;Ogaki et al, 2015;Ozawa et al, 2015;Kodama et al, 2016;Uchida et al, 2017), whereas the present study is the first to reveal the functional expression of P-gp in hiPSC-IECs. The P app value of [ 3 H]digoxin (a P-gp substrate) in the basolateral-to-apical direction was greater than that in the apical-tobasolateral one (efflux ratio, 2.43), and the differences in P app in these two directions disappeared in the presence of cyclosporin A (efflux ratio, 0.743) (Fig.…”
Section: Downloaded Fromsupporting
confidence: 50%
“…In recent years, several researchers have succeeded in generating intestinal epithelial cells from human induced pluripotent stem cells (hiPSCs) (Spence et al, 2011;Kauffman et al, 2013;Ogaki et al, 2013;Forbester et al, 2015;Iwao et al, 2015;Ozawa et al, 2015;Uchida et al, 2017). Human induced pluripotent stem cell-derived intestinal epithelial cells (hiPSC-IECs) would be a good tool to predict the absorption of oral drugs in humans, because they are reported to have the functions of transporters, such as BCRP and PEPT1, as well as of metabolic enzymes, such as CYP3A4 and CES2 (Iwao et al, 2015;Ogaki et al, 2015;Ozawa et al, 2015;Kodama et al, 2016;Kabeya et al, 2017;Uchida et al, 2017). Unlike Caco-2 cells, hiPSC-IECs show an expression pattern of CES isozymes similar to the human small intestine; CES2 is expressed at levels higher than CES1 (Kabeya et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pharmacokinetics-related gene expression and pharmacokinetic functions were insufficient using that method [14]. We have since demonstrated that mitogen-activated protein kinase, DNA methyltransferase, and transforming-growth factor-β inhibitors are useful for inducing differentiation to intestinal epithelial cells [15][16][17]. In fact, the differentiated intestinal epithelial cells we generated exhibited a wide range of pharmacokinetic functions, including drug-metabolizing enzyme activities, CYP3A4 inducibility via 1α,25-dihydroxyvitamin D 3 , and transporter activities via PEPT1 and BCRP.…”
Section: Pharmacokinetic Characteristicsmentioning
confidence: 99%
“…The formation of “rings of cells”/domes are also observed in functional enterocyte epithelium differentiated from human induced pluripotent stem (iPS) cells, which could be used to replace the Caco-2 cell model. Wound healing morphogen FGF2 treatment, the latter inhibits differentiation and prevents the formation of “ring of cells”/dome in Caco-2 cells [8, 4143]. Knockdown extracellular matrix protein which stimulates differentiation in Caco-2 cells delayed the “ring of cells”/dome formation [44].…”
Section: Data Notesmentioning
confidence: 99%